2016
DOI: 10.21916/mlr.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Labor force participation: what has happened since the peak?

Abstract: Summary of the Main ResultsSince the final quarter of 2007, the labor force participation rate has fallen from 65.9 percent to 62.8 percent in the second quarter of 2014, a decline of 3.1 percentage points. In this report, the Council of Economic Advisers estimates that this 3.1 percentage point decline can be attributed to three main sources:About half of the decline (1.6 percentage point) is due to the aging of the population.Because older individuals participate in the labor force at lower rates than younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
1
22
0
3
Order By: Relevance
“…These increased participation rates of older Americans are all the more remarkable because they came at a time when participation labor market attachment of younger and middle-aged workers has declined (Hipple 2016). Among Americans aged 25-54, labor force participation rates declined about 4 percent between 2000 and 2015 (from 92 to 88 percent for men, and 77 to 74 percent for women), in stark contrast to the significant increases among older Americans.…”
Section: What Might Concerned Potential Retirees Do?mentioning
confidence: 96%
See 1 more Smart Citation
“…These increased participation rates of older Americans are all the more remarkable because they came at a time when participation labor market attachment of younger and middle-aged workers has declined (Hipple 2016). Among Americans aged 25-54, labor force participation rates declined about 4 percent between 2000 and 2015 (from 92 to 88 percent for men, and 77 to 74 percent for women), in stark contrast to the significant increases among older Americans.…”
Section: What Might Concerned Potential Retirees Do?mentioning
confidence: 96%
“…A century-long trend toward earlier retirement came to a halt in the 1980s and now has reversed, although the rate of reversal may now be slowing down (Quinn et al 2011;Munnell 2015a). The rise in labor force participation at older ages is all the more notable because it is occurring while labor force participation among male and female workers aged 25 to 54 has declined steadily since 2000 (Hipple 2016). Older Americans represent a flexible workforce that is willing to change employers, occupations, and work intensity late in life (Johnson et al 2009;Cahill et al 2015a).…”
mentioning
confidence: 99%
“…It was established that the developed innovative potential significantly contributes to the stability of the economy during the crisis; authors suggested ways to stimulate the development of industrial production in the post-crisis period. In articles on labor force (see Hipple, 2016;Aaronson and et al, 2014), the dynamics of the volume and structure of employees of companies was analyzed, it was concluded that in the last 15-16 years there was a decrease in the number of people working in the USA, to a greater extent -teenagers and persons without higher education; forecast of changes in the labor market situation was made. In the paper of E. Bartelsman, J. Haltiwanger, S. Scarpetta (2013) the problems of estimating labor productivity were investigated, a comparative analysis of country differences and industry features was conducted, an appropriate mathematical tool was proposed, and a conclusion was made about the existence of a relationship between the volume of industry production and labor productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The LFP rate has remained slightly below 63 percent in the last two years. A closer look at the LFP rate by age, gender, and education reveals that it declined for most of the demographic groups (Hipple 2016).…”
Section: Introductionmentioning
confidence: 99%